Analisis Manajemen Zakat Infaq dan Shodaqoh di LazisNu Majelis Wakil Cabang Kandangan Temanggung - Najiyah, Nabila Lailatun; Purwanto; Wafirah, Milna (Forum Kerjasama Pendidikan Tinggi, 2023)
This research explores the implementation of zakat, infaq, and sadaqah management at the LazizNu Representative Council of the Kandangan Temanggung Branch. The research method used is descriptive qualitative, which produces data in the form of written or spoken words from interviews with the Chair and staff of the LazizNu office. Primary data sources were obtained from the field, while secondary data came from books, research journals, archives, organizational letters, and related research. Data collection techniques include interviews, observation, and documentation. The research results show that the LazizNu Representative Council of the Kandangan Temanggung Branch has successfully implemented the zakat, infaq, and sadaqah management functions. These management functions include Planning, Organizing, Implementing, and Supervising. In this way, the implementation of management functions can maximize the function of the LazizNu Kandangan Branch Representative Council.